Agritourism in don valley: Geography and institutional priorities of development - Gontar Nikolay V. (Glasnik Srpskog Geografskog Društva)
The relevance of the study lies in the reassessment of the part taken by institutions in the development of the tourism market and in the diversification of tourism supply at the regional level. In new territories of development of agritourism, it faces the challenge of not only using natural and ecological conditions, but also interacting with existing formal institutions. The purpose of this study is a structural and geographical analysis of the emerging agritourism supply in the Don Valley, and an analysis of compliance of the needs of agritourism actors with the parameters of the institutional environment. The methods of spatial analysis helped us identifying the positional features of agritourism locations in the Don Valley. Based on the measurements of accessibility, we have singled out areas of agritourism locations in the Don Valley. Analysis of business models of agritourism locations, their target segment and their integration into tourist routes made it possible for us to give a qualitative description of the agritourism areas of the Don Valley and define the nature of their involvement in agritourism. Together with the institutional analysis, this made it possible to define discrepancies between the tourism management system and the nature of agritourism development in the Don Valley. The results made it possible to formulate measures for transforming the institutional environment, and can also be useful in developing strategic documents and plans for development of agritourism in the regions diversifying the tourist supply.